2016
DOI: 10.1117/1.jmi.3.4.043504
|View full text |Cite
|
Sign up to set email alerts
|

Dose-efficient ultrahigh-resolution scan mode using a photon counting detector computed tomography system

Abstract: , "Dose-efficient ultrahighresolution scan mode using a photon counting detector computed tomography system," J. Med. Imag. 3(4), 043504 (2016), doi: 10.1117/1.JMI.3.4.043504. Abstract. An ultrahigh-resolution (UHR) data collection mode was enabled on a whole-body, research photon counting detector (PCD) computed tomography system. In this mode, 64 rows of 0.45 mm × 0.45 mm detector pixels were used, which corresponded to a pixel size of 0.25 mm × 0.25 mm at the isocenter. Spatial resolution and image noise we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 36 publications
3
108
1
Order By: Relevance
“…However, the system is usually operated using macro pixels (0.9 mm by 0.9 mm) by grouping together 4 by 4 native detector cells (0.5 mm by 0.5 mm pixel size at iso-center). To increase spatial resolution, an UHR mode was recently introduced in which 0.45 mm × 0.45 mm detector pixels were used, which corresponded to a pixel size of 0.25 mm × 0.25 mm at the iso-center [13]. This mode, however, only had one energy threshold and therefore lacked energy discrimination information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the system is usually operated using macro pixels (0.9 mm by 0.9 mm) by grouping together 4 by 4 native detector cells (0.5 mm by 0.5 mm pixel size at iso-center). To increase spatial resolution, an UHR mode was recently introduced in which 0.45 mm × 0.45 mm detector pixels were used, which corresponded to a pixel size of 0.25 mm × 0.25 mm at the iso-center [13]. This mode, however, only had one energy threshold and therefore lacked energy discrimination information.…”
Section: Methodsmentioning
confidence: 99%
“…The same 14 renal stones with mixed compositions were also used to assess the influence of spatial resolution and image noise in dual energy applications. Dual-energy analysis was performed to differentiate stone composition and quantify the amount of UA and NUA based on the CT number ratio (CTR) of each pixel inside the stone, which was calculated as the ratio of the CT numbers in the low-energy bin (25 to 75 keV) to those in the high-energy bin (75 to 140 keV) [13]. The results were compared with the reference standard achieved with microCT scans [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two ultra-high-spatial-resolution imaging modes, with detector size of 0.25 mm × 0.25 mm at the iso-center, are available. This enables simultaneous multi-energy CT data acquisition with image thickness of 0.25 mm [12, 13]. Detailed descriptions of the system can be found elsewhere [5].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, photon-counting detectors do not suffer from the fill factor limitations inherent to the traditional energy-integration detectors, thereby allowing the design of smaller detector pixels to achieve dose-efficient high resolution CT without the need for comb/grid filters. Recently Leng et al 1,2 demonstrated the high resolution acquisition modes of a whole-body research PCD-CT system. Due to smaller per-pixel area in combination with narrow energy bin required for higher image contrast and better spectral sampling, the high resolution modes are inherently prone to higher noise levels in the energy bin images.…”
Section: Introductionmentioning
confidence: 99%